Mechanical, Thermal, And Rheological Properties of Nano-Calcium Carbonate/Polypropylene Composites Modified Bymethacrylic Acid - Beg, M. D. H.; Zaman, Haydar U. (SAGE Publications, 2016)
Polypropylene (PP)/nano-calcium carbonate (nCC) composites modified with methacrylic acid (MA) with and without dicumyl peroxide (DCP) were prepared by a twin-screw extruder. The effects of nCC and MA on the mechanical, thermal, and rheological properties of PP/nCC composites were investigated. The mechanical tests indicating that nCC could simultaneously reinforce and toughen PP. In addition, incorporation of MA further increased the mechanical properties of the composites. In the presence of DCP, a small amount of MA could increase markedly the mechanical properties of PP/nCC composites. Differential scanning calorimetry results indicate that the addition of nCC increased the crystallization temperature (T c) as a result of heterogeneous nucleation effect of nCC on PP and can induce β-phase PP. The addition of MA can further increase the T c of PP and the intensity of β-phase PP. The results of rheological property analysis indicated that the viscosity increased with increasing amount of the filler, especially at low shear rates. The addition of MA improved the dispersion of nCC resulting in the increasing of apparent viscosity.